Holy Quran and Scientific Facts - Latif, Muhammad Muqarrab; Bhatti, Asif Hussain; Mariam, Namra (International Journal of Islamic Khazanah, 2024)
A remarkable array of facts about the universe—spanning cosmology, biology, physics, geology, and other disciplines—are mentioned in the Holy Quran, a text revealed approximately fourteen centuries ago. Many of these statements have only been understood and confirmed with the advent of modern science and technology. This article explores the consonance between scientific discoveries and Quranic verses, addressing key topics such as the origin, eventual fate, and recycling of the universe; the formation of iron; the geological significance of mountains; the role of the frontal lobe in human behavior; and the mechanisms of pain perception. By examining these subjects, this study underscores the alignment between the Quranic descriptions and contemporary scientific knowledge, dispelling misconceptions that religious texts promote conservative thinking or hinder the understanding of the physical universe. The findings suggest that the Holy Quran complements scientific inquiry rather than contradicting it, fostering a deeper appreciation of both science and spirituality.